Colonoscopic Diagnosis and Medical Management of Neutrophilic Colitis in a Dog - Sakthikarthikeyan, Sengamani; Ponnuswamy, Kallipatti Karuppusamy; Sivaseelan, Soundarapandian; Ramprabhu, Rajah Arunachalam (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
Colitis is defined as the inflammation of the colon and is the most common cause of significant bowel diarrhea. The colon plays a vital role in conserving water and electrolytes and acts as the primary site of fecal storage until expulsion is necessary. Disruptions of the normal homeostasis of the colon may lead to disturbances in both absorption and motility